Wing Simulation Using Naca 0018 and 0024 and Aluminum Alloy 7075 T6-SN and 7050-T7451 Materials for Lift and Drag - Pane, Medyawanti (Universitas Medan Area, 2024)
Analysis of the airfoil's shape on an airplane wing is essential because geometry can determine aerodynamic performance and the forces at work, such as lift and drag. In this research, two types of aluminum materials, namely Aluminum Alloy 7075 T6-SN and Aluminum Alloy 7050-T7451, will be tested to find out which one can produce the highest lifting force and drag force on NACA 0018 and 0024 as well as look at the pressure contour and speed Contour of each type of material using ANSYS Fluent software at a speed of 200 m/s. From the simulation and calculation results, it was obtained that the highest lift coefficient and drag coefficient on the NACA 0018 Airfoil were using Aluminum Alloy 7075-T6 SN material, namely 6.83 N and 6.89 N. Meanwhile, in the NACA 0024 Airfoil simulation, the highest lift coefficient and thrust coefficient were obtained. It also uses aluminum Alloy 7075-T6 SN, namely 3.23 N and 4.64 N.